You are on page 1of 2

# Ejercicios

:
𝒅𝒚 𝒅𝒚 𝟐 𝟏
) 𝒚 = 𝒙 ( ) + 𝟐 ( )
𝒅𝒙 𝒅𝒙 𝑑𝑦

=𝑝 𝑑𝑥 𝑦

= 𝑥 𝑃 + 2 𝑃2 𝑑𝑦

= 𝑥𝑃′ + 𝑃 + 4𝑃𝑃′ 𝑑𝑥 𝑃

+ 𝑥𝑃′ + 𝑃 + 4𝑃𝑃′
0 =𝑥𝑃′ + 4𝑃𝑃′
0 = 𝑝′ (𝑥 + 4𝑝) 𝑃
′ = 0 𝑝
=𝑐 𝑦

= 𝑥𝑐 + 2𝑐 2 𝑺𝒐𝒍: 𝑮𝒆𝒏𝒆𝒓𝒂𝒍 𝑥
+ 4𝑃 = 0
𝑥 𝑝
=−
4
𝑥 𝑥 2 𝑦
= 𝑥 (− ) + 2 (− )
4 4
𝑥 2 2𝑥 2 𝑦
= − +
4 16
𝑥 1 2𝑥 2 𝑦
=− +
4 8
𝑥2 𝑦
=− 𝑆𝑜𝑙 𝑒𝑠𝑝𝑒𝑐í𝑓𝑖𝑐𝑎
8
𝒅𝒚 𝒅𝒚 𝒅 𝒅 𝟐
)𝒚 = 𝒙 𝒅𝒙 + 𝒇(𝒅𝒙) 𝒅𝒙
= 𝒖𝒗 = 𝒖′ 𝒗 + 𝒖𝒗′ 𝒅𝒙
= 𝒗𝒏 = 𝒏𝒗𝒏−𝟏 𝒗′
𝒅𝒚 𝑦
= 𝑥𝑦 ′ − (𝑦 ′ )4 𝑷 = 𝒅𝒙 𝒑 = 𝒚′ 𝑥 − 4𝑃3 = 0 𝑦

= 𝑥𝑃 − 𝑃4 𝑥 = 4𝑃3 𝑦

′ = 𝑃 + 𝑥𝑃′ − 4𝑃3 𝑃′ 4𝑃3 = 𝑥
𝑥 𝑃
= 𝑃 + 𝑥𝑃′ − 4𝑃3 𝑃′ 𝑝3 =
4
1
′ 3 ′ 𝑥 2
0 = 𝑥𝑃 − 4𝑃 𝑃 𝑃= (4 )
1
′ 3 ′ 𝑥 3 𝑥𝑃
− 4𝑃 𝑃 = 0 𝑦= 𝑥 (4 ) −
4
𝑥 3
( ) 𝑠𝑜𝑙 𝑒𝑠𝑝𝑒𝑐í𝑓𝑖𝑐𝑎
4

𝑝′ (𝑥 − 4𝑃3 ) = 0 𝑝′ = 0 𝑝′ = 0 𝑝=𝑐 𝑥 − 4𝑃3 = 0 𝑦 = 𝑥𝑐 − 𝑐 4 𝑆𝑜𝑙 𝑔𝑒𝑛𝑒𝑟𝑎𝑙 ′ 3) 𝒚 = 𝒙𝒚′ − 𝒆𝒚 𝑦′ = 𝑝 𝑦 = 𝑥𝑝 − 𝑒 𝑝 𝑦 ′ = 𝑝 + 𝑥𝑝′ − 𝑒 𝑝 𝑝′ 𝑝 = 𝑝 + 𝑥𝑝′ − 𝑒 𝑝 𝑝′ 0 = 𝑥𝑝′ − 𝑒 𝑝 𝑝′ 0 = 𝑝′ (𝑥 − 𝑒 𝑝 ) 𝑝′ = 0 𝑝=𝑐 𝑦 = 𝑥𝑐 − 𝑒 𝑐 𝒔𝒐𝒍: 𝒈𝒆𝒏𝒆𝒓𝒂𝒍 𝑥 − 𝑒𝑝 = 0 𝑥 = 𝑒𝑝 𝑙𝑛𝑥 = 𝑙𝑛𝑒 𝑝 𝑙𝑛𝑥 = 𝑝 𝑦 = 𝑥𝑙𝑛𝑥 − 𝑒 𝑙𝑛𝑥 𝑦 = 𝑥𝑙𝑛𝑥 − 𝑥 𝑦 = 𝑥(𝑙𝑛𝑥 − 1) 𝑺𝒐𝒍: 𝒆𝒔𝒑𝒆𝒄í𝒇𝒄𝒂 4) 𝒚 = 𝒙𝒚′ + 𝟏 − 𝒍𝒏𝒚′ 𝑦′ = 𝑝 𝑦 = 𝑥𝑝 + 1 − 𝑙𝑛𝑝 1 𝑦 ′ = 𝑝 + 𝑥𝑝′ − 𝑝′ 𝑝 1 𝑝 = 𝑝 + 𝑥𝑝′ − 𝑝′ 𝑝 1 0 = 𝑥𝑝′ − 𝑝′ 𝑝 1 0 = 𝑝′ (𝑥 − ) 𝑝 ′ 𝑝 =0 𝑝=𝑐 𝑦 = 𝑥𝑐 + 1 − 𝑙𝑛𝑐 𝑆𝑜𝑙: 𝐺𝑒𝑛𝑒𝑟𝑎𝑙 1 𝑥− =0 𝑝 1 𝑝= 𝑥 1 1 𝑦 = 𝑥 + 1 − 𝑙𝑛 𝑥 𝑥 1 𝑦 = 1 + 1 − ln 𝑥 1 𝑦 = 2 − ln 𝑠𝑜𝑙. 𝑒𝑠𝑝𝑒𝑐í𝑓𝑖𝑐𝑎 𝑥 .